Optimization of sustainable concrete properties modified with blends of date palm ash and eggshell powder using response surface methodology. - Musa Adamu; Yasser E. Ibrahim; Hani Alanazi (Developments in the Built Environment, 2024)
Agricultural waste products are one of the major solid wastes disposed into landfills without treatment or recycling. In this study, date palm ash (DPA) was processed from date tree waste and used to partly substitute cement in dosages of 0 %, 10 %, 20 %, 30 %, and 40 %. To counteract the slow pozzolanic reaction of the DPA, eggshell powder (ESP) was added in amounts of 0 %, 1 %, 2 %, 3 %, and 4 % by mass of binder. Response surface methodology (RSM) was used for designing experimental mixes, optimization and establishing statistical models for predicting the properties of the concrete. Blending DPA and ESP as hybrid binder materials in concrete improved its mechanical properties and reduced its water absorption. The RSM models established were very significant, having high accuracy and average error lower than 6 %. From the optimization, blending 14.77 % DPA and 2.2 % ESP gave the best performance in the concrete properties with desirability of 91.1 %.